2021
DOI: 10.31617/visnik.knute.2021(140)08
|View full text |Cite
|
Sign up to set email alerts
|

Digital Functionality of Complementation of Business Processes of the Hotel Industry

Abstract: It has been determined that intensive digitalization of service processes is a condition for the effective functioning of the hotel industry under the influence of the COVID-19 pan­demic. One of its important directions, namely the use of a process approach to management, has been specified. The article proves that the improvement of business processes on the basis of their complementation and defining its digital functionality will enable to improve the quantitative and qualitative performance, will help to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to Chalupa et al (2021), Petricek (2020), € Ozdemir et al (2019), Yesipova and Burak (2013) and March and Fugazi (2002), BPM which of a major determinant focus on BPs can be implemented by hotel industry as a new way to achieve a high level of service quality and maintain a competitive advantage by reducing errors in hotel operating processes, eliminating nonvalue adding activities and improving customer satisfaction. The use of a process approach to management is an important direction of effective functioning of hotel business for a better, deeper and more comprehensive understanding of processes and identifying problematic areas or inefficiencies in hotel operations (Fuhrken, 2022;Han et al, 2020;Yevheniia et al, 2021).…”
Section: Bpm In Hotel Industrymentioning
confidence: 99%
See 3 more Smart Citations
“…According to Chalupa et al (2021), Petricek (2020), € Ozdemir et al (2019), Yesipova and Burak (2013) and March and Fugazi (2002), BPM which of a major determinant focus on BPs can be implemented by hotel industry as a new way to achieve a high level of service quality and maintain a competitive advantage by reducing errors in hotel operating processes, eliminating nonvalue adding activities and improving customer satisfaction. The use of a process approach to management is an important direction of effective functioning of hotel business for a better, deeper and more comprehensive understanding of processes and identifying problematic areas or inefficiencies in hotel operations (Fuhrken, 2022;Han et al, 2020;Yevheniia et al, 2021).…”
Section: Bpm In Hotel Industrymentioning
confidence: 99%
“…However, BPM efforts in the hotel industry is weakly examined by researchers in literature (Han et al, 2020;Yevheniia et al, 2021;Xuhua et al, 2018), which justified by Vergidis et al (2008) that service managers may be not convinced that a process-based approach (BPM) could bring significant tangible and measurable benefits compared to the manufacturing sector, as a result to the lack of clear understanding regarding service processes and related quality parameters and how to put them into practice (Srinivasu et al, 2011;Antony and Taner, 2003;Fotopoulos and Psomas, 2009). Furthermore, some of the certain inherent characteristics of service operations and the non-conformity exist in quality characteristics of manufacturing and service processes cannot give way to the application of traditional production management techniques and approaches such as BPM initiatives and increase the complexity of quality control and improvement efforts (MacCarthy and Wasusri, 2002;Goh, 2014;Jankowski-Guzy et al, 2018;Antony, 2004).…”
Section: Bpm In Hotel Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…However, BPM implementation in the hotel industry is less frequent (Han et al, 2021;Yevheniia et al, 2021), and only a few studies focusing on this topic can be found. In addition, management literature report relatively limited instances of potential applications of BPM in hospitality industry, especially hotels.…”
mentioning
confidence: 99%